Unravelling Persistent Problems to Transformative Marine Governance - Kelly, Christina; Ellis, Geraint; Flannery, Wesley (Frontiers in Marine Science, 2019)
Coasts are dynamic socio-ecological systems, subject to increasing anthropogenic pressures that present complex challenges for the design of effective coastal and marine governance systems. There are many contributing factors to the unsustainability of the marine environment, including weak governance arrangements. Typically, the management of coastal and marine ecosystems is undertaken in a fragmented way, with responsibilities dispersed across a number of bodies. ‘Integrated management’ is often proposed in normative approaches to marine management as a mechanism for securing more sustainable outcomes. The implementation of integrated management, however, tends to occur within existing governance structures and fails to address deep-rooted issues such as path dependency, institutional inertia and policy layering. These barriers to transformative marine governance are re-framed in this paper as ‘persistent problems’ which inhibit more holistic approaches to achieve effective integrated management. Using insights from two Irish case studies to show how the implementation of innovative local initiatives for sustainable coastal and marine management are constrained by persistent institutional problems, it is concluded that an alternative management paradigm is required to understand and address the complexities involved in the design and delivery of an integrated management regime.